Pendekatan One Health Dalam Peningkatan Akses Dan Kualitas Air Bersih Di Gereja Advent Kampung Bibiosi, Kabupaten Keerom - Assa, Inriyanti; Rumbiak, Helmin; Rupilu, Vrensca; Asmuruf, Frans; Dian Burdames, Galio Rudolf (The Community Engagement Journal, 2025)
The main purpose of this activity to improve access and quality of clean water for the community around the Bibiosi Village Adventist Church, Keerom Regency, through the implementation of a One Health approach that integrates human, environmental, and social health aspects. Bibiosi Village faces serious problems related to limited clean water sources. Most residents still rely on river water and open wells that have high levels of turbidity and are contaminated with pathogenic microorganisms, especially Escherichia coli. This condition causes a high incidence of air-borne diseases such as diarrhea, skin infections, and digestive disorders. Low levels of clean and healthy living behavior (PHBS), limited infrastructure, and the habit of defecating in the open exacerbate the situation. This community service program uses a participatory approach by involving church congregation members, community leaders, housewives, church youth, and local health workers. The implementation of the activity is divided into four main stages, namely (1) socialization, (2) drilling and making wells, (3) installing air installations, and (4) implementing Reverse Osmosis (RO)-based water treatment technology. From a One Health perspective, this activity emphasizes the importance of the relationship between human, environmental, and animal health. Protection of air sources and waste management are part of an integrated health system. Keywords: health, people, environment, social